Gas-phase ozonolysis of trans-2-hexenal: Kinetics, products, mechanism and SOA formation. (15th May 2021) - Grira, A.; Kalalian, C.; Illmann, J.N.; Patroescu-Klotz, I.; El Dib, G.; Coddeville, P.; Canosa, A.; Coeur, C.; Wiesen, P.; Roth, E.; Chakir, A.; Tomas, A.
Abstract: In this work, kinetics, product formation, chemical mechanism and SOA formation for the gas-phase reaction of trans-2-hexenal (T2H) with O3 are examined using four complementary experimental setups at 298 ± 2 K and atmospheric pressure. Product studies were conducted in two contrasted experimental conditions, with and without OH radical scavenger. The ozonolysis rate constant was determined in both static and dynamic reactors. An average reaction rate constant of (1.52 ± 0.19) × 10 −18 cm 3 molecule −1 s −1 was determined. Glyoxal and butanal were identified as main products with molar yields of 59 ± 15% and 36 ± 9%, respectively, in the presence of an OH scavenger. Slightly lower values were obtained in the absence of scavenger. Acetaldehyde, propanal and 2-hydroxybutanal were also identified and quantified. A reaction mechanism was proposed based on the observed products. SOA formation was observed with aerosol mass yields >13% for SOA masses of 400 μg m −3 . This work demonstrates for the first time that 2-alkenals ozonolysis can be a source of SOA in the atmosphere. Highlights: Trans-2-hexenal ozonolysis kinetics and products investigated. A reaction mechanism is proposed. First secondary organic aerosol investigation.